2017
DOI: 10.1007/s12663-017-1046-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy of Transalveolar Screws and Conventional Dental Wiring Using Erich Arch Bar for Maxillomandibular Fixation in Mandibular Fractures

Abstract: We found that transalveolar group offered advantages like less time taken with a definite decreased risk of percutaneous injury, while the iatrogenic complications like dental damage can be reduced by taking adequate precautions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…27,30 This data suggests that there is a high risk of communication of blood borne diseases when arch bar is used for IMF. On the contrary, 4 studies reported mucosal coverage 12,28 30 and 5 studies reported tooth mobility with the use of IMF screws. 13,27 30 These complications were not seen when arch bar was used; only 2 teeth crowns were damaged while using arch bar.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…27,30 This data suggests that there is a high risk of communication of blood borne diseases when arch bar is used for IMF. On the contrary, 4 studies reported mucosal coverage 12,28 30 and 5 studies reported tooth mobility with the use of IMF screws. 13,27 30 These complications were not seen when arch bar was used; only 2 teeth crowns were damaged while using arch bar.…”
Section: Resultsmentioning
confidence: 89%
“…A total of 6 studies have reported about the various complications in both the groups (Table 4). Needle stick injury or glove perforation was reported by 5 studies and was seen in Arch Bar group in all the studies, 12,13,27,29,30 whereas only 2 studies had needle stick injuries or glove perforations in IMF screw group. 27,30 This data suggests that there is a high risk of communication of blood borne diseases when arch bar is used for IMF.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations